Pemberdayaan Perempuan Desa Melalui Pelatihan Pemanfataan Lidi Sawit Menjadi Produk Di Kampung Sungai Tengah Kecamatan Sabak Auh Kabupaten Siak - Adianto, Adianto; Habibie, Dedi Kusuma; Putri, Risky Arya; Indry, Indry; Utami, Ayu Tri (Universitas Pahlawan Tuanku Tambusai, 2024)
This service activity was carried out in the form of empowerment for women in Sungai Tengah Village in an effort to contribute new economic sources for the village community based on the village's potential. The stages of this activity are carried out through: 1). Identification of the potential of palm sticks in the village and village women who will be trained. 2). Implementation of village women empowerment through training on the utilization of palm sticks into products. 3). Formation of a group of women palm stick craftsmen in Sungai Tengah Village. Implementation of activities in the form of training for women or mothers in Sungai Tengah Village in utilizing palm sticks into handmade products, such as plates, rice baskets and fruit shells